(untitled) (ModaPalavra e-periódico, 2024)
The text explores the dynamics of dialogue between digital fashion influencers and followers on Instagram, highlighting the usefulness of this relationship in fashion consumption. For influencers, interaction is a source of inspiration, evidenced by feedback and engagement from followers. In the Brazilian context, followers use influencers as a fashion reference, especially in affordable fashion purchases and replicas, given the economic disparity. A survey, carried out through Netnography, reveals that Instagram is the main platform for this interaction, despite its weaknesses. Strategies are innovative to overcome these limitations, such as the use of other platforms, reading clubs and in-person meetings. For smaller influencers, Instagram resembles a relationship marketing tool, while for mega influencers it is perceived as an updated version of television. The article draws attention to the importance of brands valuing influencers who know how to establish dialogue with their followers, since dialogue is a vital force in creating meaning and cohesion in a globalized society.